Study on Route Optimization of Methanol Safety Transportation Routing - Li Liu (Chemical Engineering Transactions, 2017)
Optimal routing is an important part of the methanol road transportation research. Optimal routing of methanol is different from those general optimal routing processes. Methanol optimal routing need to take into account the risk of path, the possible consequences of the accident and emergency response capabilities around the path and other factors This paper includes two aspects of research, one is the risk analysis of methanol road transportation, the other is optimal routing based on risk assessment.